HUBUNGAN PENGETAHUAN IBU TENTANG GIZI ANAK USIA 0â5 TAHUN DENGAN STATUS GIZI ANAK (STUDI ANALITIK DI POSYANDU DUSUN SUKABUMI DESA SIMAN KECAMATAN KEPUNG TAHUN 2008) - Sukatmi, Sukatmi; Nugroho, Christianto; Agustina, Erni (Akademi Keperawatan Pamenang, 2010)
NutritionÂ statusÂ ofchildÂ representÂ situationÂ ofÂ bodyÂ asÂ effectÂ ofÂ consumptionÂ andÂ usageÂ ofnutritionAgechild of under five year represent factionwhich is to anger easily to problem of and health ofnutritionamongothersÂ isÂ problemÂ lessÂ proteinÂ energyrepresentingÂ theÂ problemÂ ofÂ especialnutritioninÂ Indonesia.Â IntentionÂ ofthisÂ researchÂ isÂ toÂ identifyÂ relationÂ linkÂ knowledgeÂ ofÂ motherÂ aboutÂ ageÂ child nutrition0-5Â yearÂ withÂ statusÂ ofnutritionchild in Posyandu of Sukabumi Countryside of Siman District Besiege year 2008.The researchdesign iscorrelation study with population counted 37 and people of sample 34 responderwithÂ dataÂ samplingÂ consecutive,Â collectedÂ byÂ givingÂ questionnaireatÂ motherÂ andÂ observationÂ ofÂ heavyÂ child.AfterwardsÂ dataanalyzedby using correlation test of spearman with value of significance0,05.From result of research got by most good enough knowledgeable mother bring in hand age child nutrition0-5Â yearÂ thatÂ isÂ equaltoÂ 58.8%Â andÂ mostÂ statusÂ of childnutrition inÂ levelÂ ofÂ good nutritionÂ is55,9%.Â FromresultÂ ofÂ correlationÂ testÂ ofÂ spearmanÂ gotÂ byÂ valueÂ ofÂ significance0,263Â >Â 0,05Â meaningÂ H0Â accepted.Â Thismatter explain that do not there are relation link among between knowledge of mother about age child nutrition0-5 year with status ofchild nutrition.TheknowledgeonÂ theÂ childÂ nutritionÂ arevitalÂ importanceÂ ownedÂ byÂ mother,Â inÂ orderÂ toÂ canÂ correctupbringing atits ducky especially in accomplishment of its requirement of him. But, knowledge had by mother isnot solely absolutefactor influence its child nutrition status. Because there is many other factor, like economicstatus of family, food sanitation, appetiteeat, amount and many other factor.